Providing Health Care to HIV Patients in Southern Africa - Haacker, Markus (Washington, D.C. : International Monetary Fund, 2001)
The paper provides an economic analysis of the impact of HIV/AIDS on the health sector i Southern Africa. It provides indicators for the scale of the impact, including estimates of translator costs of various forms treatment. In anticipation of increasing numbers of patients with HIV/AIDS-related diseases, it is essential to expand the already strained health facilities ar to substantially increase the training of health personnel. While proposed reductions in the prices of antiretroviral therapies will considerably expand the range of those who can affor them, they will remain accessible to a minority of the population only.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet